We've Got a Gun?: Comparing Reports of Adolescents and their Parents about Household Firearms - Cook, Philip J (2007)
Firearms are a leading cause of mortality among adolescents, and the guns that adolescents use to harm themselves or others often come from their own homes. In this statewide, multi-language, community-based survey of 5,704 co-residing pairs of adolescents and their parents, we asked about guns in the home and compared their responses. The proportions of parents and adolescents responding affirmatively were similar: 25.7% and 26.8%, respectively, for any guns; 15.0% and 13.2%, respectively, for handguns. A paired analysis documented substantial agreement for whether there was any gun in the home and less agreement about whether there was a handgun in the home. The amount of agreement and disagreement was related to household composition and gender of the respondents. The disagreement was substantial for some groups (e.g., when boys residing in households containing a single mother and no other adults reported that there was a gun in the home, 64.8% of their mothers said that there was not a gun in the home). Implications for research and intervention are discussed